First-line immune-checkpoint inhibitor plus chemotherapy versus chemotherapy alone for extensive-stage small-cell lung cancer: a meta-analysis. (December 2020) - Landre, Thierry; Chouahnia, Kader; Des Guetz, Gaëtan; Duchemann, Boris; Assié, Jean-Baptiste; Chouaïd, Christos
Introduction: Platin-based chemotherapy (CT) has long been the first-line standard-of-care for patients with extensive-stage small-cell lung cancer (ES–SCLC). Adding immune-checkpoint inhibitor(s) to CT (ICI+CT) in this setting is an option of interest, although its benefit is apparently modest. Methods: This meta-analysis was conducted on randomized trials comparing first-line ICI+CT versus CT alone for ES–SCLC. Outcomes included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), response at 12 months and adverse events (AEs). Subgroup analyses were computed according to the immunotherapy used, performance status (PS), age, platinum salt, liver metastases and brain metastases at diagnosis. Results: The literature search identified one randomized phase II (ECOG-ACRIN-5161) and four phase III trials (CASPIAN, IMPOWER-133, KEYNOTE-604 and Reck et al. 2016) that included 2775 patients (66% males, 95% smokers, median age: 64 years, PS = 0 or 1). ICI+CT was significantly associated (hazard ratio [95% confidence interval]) with prolonged OS [0.82 (0.75–0.89); p < 0.00001] and PFS [0.81 (0.75–0.87); p < 0.00001], with OS benefits for anti-PD-L1 [0.73 (0.63–0.85); p < 0.0001] or anti-PD-1 [0.76 (0.63–0.93); p < 0.006] but not for anti-CTLA-4 [0.90 (0.80–1.01), p = 0.07]. ORRs for ICI+CT or CT alone were comparable [odds ratio 1.12 (0.97–1.00); p = 0.12], but responses at 12 months favored ICI+CT [4.16 (2.81–6.17), p < 0.00001]. Serious grade-3/4 AEs were more frequent with ICI+CT [odds ratio 1.18 (1.02–1.37); p = 0.03]. Compared with CT, no ICI+CT benefit was found for ES–SCLC with brain metastases at diagnosis [HR 1.14 (0.87–1.50); p = 0.34]. Conclusions: First-line ICI+CT appears to be superior to CT alone for ES–SCLC except for patients with brain metastases at diagnosis.